Konsep Pembiayaan Perumahan bagi Masyarakat Berpenghasilan Rendah di Kecamatan Ngaliyan - Bony Djosman; Asnawi Manaf (Jurusan Perencanaan Wilayah dan Kota, 2016)
One of the basic things that human needs is shelter. Shelter is usually represented by house. Government have obligation to guarantee all people for having proper and affordable house. There are issue in both housing production and housing consumption for low income segment. Lack of ability to pay proper house with affordable cost is problem that low income people problem had to face. Housing finance system that already available is not suit for low income people’s characteristic. Ngaliyan District is surrounded by Industrial zone and near from Kendal Regency, so there are many chance there are peoples who work in factory and informal sector. Purpose for this research to review housing finance support and plan suitable housing finance concept for low-income people ini Ngaliyan. Qualitative approach by depth interview is research method for this journal. Community based finance concept is suit for low income by adding government’s program (Ministry of Public Works and Public Housing) that already available like FLPP, BSPS, BUM and PSU stimulant. The output is two concept. That two concept are self-helping concept and FLPP concept. Housing finance concept is created by connected four supported finance and the maximize them.